The role of medial prefrontal cortex in early social cognition - Grossmann, Tobias (Frontiers in Human Neuroscience, 2013)
One major function of our brain is to enable us to behave with respect to socially relevant information. Much research on how the adult human brain processes the social world has shown that there is a network of specific brain areas, also called the social brain, preferentially involved during social cognition. Among the specific brain areas involved in the adult social brain, functional activity in prefrontal cortex (PFC), particularly the medial prefrontal cortex (mPFC), is of special importance for human social cognition and behavior. However, from a developmental perspective, it has long been thought that PFC is functionally silent during infancy (first year of life), and until recently, little was known about the role of PFC in the early development of social cognition. I shall present an emerging body of recent neuroimaging studies with infants that provide evidence that mPFC exhibits functional activation much earlier than previously thought, suggesting that the mPFC is involved in social information processing from early in life. This review will highlight work examining infant mPFC function across a range of social contexts. The reviewed findings will illustrate that the human brain is fundamentally adapted to develop within a social context.